Rancang Bangun Antena Mikrostrip Patch Segi Empat Multiband Pada Frekuensi 2,1 , 2,6 , 2,8 dan 3,3 GHz - Sri Indah Rezkika (Prodi Teknik Informatika (S1) Institut Teknologi dan Bisnis Indonesia, 2023)
Multiband antenna is a type of antenna that can work simultaneously at four different frequency ranges without the need for four physically different antennas. This paper describes the design of multiband rectangular patch microstrip antennas for various applications, namely 3G, LTE, RFID and WIMAX. The antenna measurement results show that at a frequency of 1.945 GHz - 2.394 GHz, a bandwidth of 449 MHz is obtained. The second frequency works from 2.635 GHz – 2.706 GHz to obtain a wide bandwidth of 71 MHz. The third frequency works from 2.768 GHz – 2.862 GHz to obtain a wide bandwidth of 94 MHz. The fourth frequency works from 3.249 GHz – 3.480 GHz to obtain a wide bandwidth of 231 MHz with each frequency obtaining a VSWR value ≤ 2.